Identifikasi Jenis Kuskus di Cagar Alam Gunung Fafinesu Kabupaten Timor Tengah Utara, Nusa Tenggara Timur - Gonsianus Pakaenoni (SAINTEKBU, 2022)
Lack of scientific information and the absence of research on the diversity and distribution of cuscus species in Timor Island in general and North Central Timor Regency in particular, it is necessary to make various basic efforts to provide data and information on the types of cuscus on Timor Island, especially in North Central Timor District. This research was conducted in Nature Reserve of Gunung Fafinesu with an altitude of 932-1200 m a.s.l. The method used in this research is to use descriptive methods with field observation techniques and semi-structural interviews. The results of interviews with key respondents, there are two species of cuscus, namely Phalanger orientalis and Phalanger vestitus, the results of direct observations in Nature Reserve of Gunung Fafinesu found 6 individuals belonging to Phalanger orientalis, while Phalanger vestitus when direct observation was not found. These results indicate that the number of cuscus in Nature Reserve of Gunung Fafinesu is decreasing over time and / or has approached extinction. For this reason, the Government of North Central Timor Regency needs to prepare an area that can be used as an ex situ conservation area for wild animals which are increasingly heading towards extinction, besides that there needs to be a socialization to the public about the types of protected animals so that the community will have more awareness to no longer hunt these animals.